Structural conformation and self‐assembly process of p31‐43 gliadin peptide in aqueous solution. Implications for celiac disease. (23rd November 2019) - Herrera, María Georgina; Gómez Castro, María Florencia; Prieto, Eduardo; Barrera, Exequiel; Dodero, Veronica Isabel; Pantano, Sergio; Chirdo, Fernando
Abstract : Celiac disease (CeD) is a highly prevalent chronic immune‐mediated enteropathy developed in genetically predisposed individuals after ingestion of a group of wheat proteins (called gliadins and glutenins). The 13mer α‐gliadin peptide, p31‐43, induces proinflammatory responses, observed by in vitro assays and animal models, that may contribute to innate immune mechanisms of CeD pathogenesis. Since a cellular receptor for p31‐43 has not been identified, this raises the question of whether this peptide could mediate different biological effects. In this work, we aimed to characterize the p31‐43 secondary structure by different biophysical and in silico techniques. By dynamic light scattering and using an oligomer/fibril‐sensitive fluorescent probe, we showed the presence of oligomers of this peptide in solution. Furthermore, atomic force microscopy analysis showed p31‐43 oligomers with different height distribution. Also, peptide concentration had a very strong influence on peptide self‐organization process. Oligomers gradually increased their size at lower concentration. Whereas, at higher ones, oligomers increased their complexity, forming branched structures. By CD, we observed that p31‐43 self‐organized in a polyproline II conformation in equilibrium with β‐sheets‐like structures, whose pH remained stable in the range of 3–8. In addition, these findings were supported by molecular dynamics simulation. The formation of p31‐43 nanostructures with increased β‐sheet structure may help to explain the molecular etiopathogenesis in the induction of proinflammatory effects and subsequent damage at the intestinal mucosa in CeD. Abstract : The p31‐43 gliadin peptide induces proinflammatory responses that may contribute to innate immune mechanisms in celiac disease pathogenesis. Here, using spectroscopic, microscopic, and in silico techniques, we demonstrated that p31‐43 is able to self‐assemble and this process is dependent on time and peptide concentration. Its conformation showed a polyproline II structure in equilibrium with β‐turns and β‐sheet like ones. These findings help understand the structural features of this toxic peptide.